A Study in SCOPUS bibliometric on finance in the period 2004-2011 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2013)
The importance of searches for lines of research in the academic databases of universities is crucial to improve the scientific management of the various researchers organized in academic groups of their respective academic units. Knowledge of recent years authors have conducted studies on finance is relevant in scientific articles bibliographic search of this issue in SCOPUS in the period 2004-2011, given that it allows those investigating financial problems to know what the new financial theories are at the frontier of knowledge and are developing in recent days to thereby raise issues of academic research bodies and the various graduate programs to which they belong. The search strategy was on finance SCOPUS to know how many articles have been published, its authors, number of publications by author, subject areas, types of documents, journals, keywords, authors' institutional affiliation, country and language. To design networks crosses authors were developing SQL statements with Visual Fox Pro 6.0 and 5.1 CmaapTools. Were 12 networks in total, we analyze the 5 biggest, most publications the authors had in 2004-2011 belong to networks, hence the importance of collaborative work, in the analyzed networks are studied and published international finance topics, financial institutions, finance and law, the evolution of finance, portfolio theory, financial markets and portfolio selection.
Keywords: financial theories; scientific articles; financial investigators